Correlation holes and slow dynamics induced by fractional statistics in gapped quantum spin liquids - Oliver Hart (Nature Portfolio, 2021)
Clear experimental signatures of fractional statistics in topologically ordered phases have been lacking. Here, the authors predict detectable signatures of non-trivial mutual statistics of fractionalized excitations in gapped topological quantum spin liquids at finite temperature.